Fragile Heterosexuality: A Cross-cultural Study Between Germany and Italy - Guevara, Martha Lucia Borras; West, Keon; Brambilla, Marco; Bruckmüller, Susanne (Sexuality and Culture, 2022)
Prior research in the UK and the USA found that heterosexual identity was perceived as more easily compromised than gay identity: a finding dubbed the "Fragile Heterosexuality " effect. However, there is as yet no evidence that this effect occurs outside the USA and UK. With representative samples from Germany (N = 1236) and Italy (N = 1249), we investigated the fragile heterosexuality effect using participants' agreement with gender-neutral statements about the perceived fragility of sexual orientation of others. We found evidence supporting the fragile heterosexuality effect in both countries. We also investigated six possible moderators of the effect. Higher estimates of gay/lesbian population weakened the effect, and higher levels of anti-gay prejudice strengthened the effect. Contact (quantity/quality), right wing authoritarianism, and social dominance orientation did not moderate the effect. These findings contribute to previous literature by highlight that the fragile heterosexuality effect appears across countries of diverse LGBTQ friendliness and languages, and also suggest plausible explanations for the effect.
CRIS-Team WoS Importer:2023-01-27